The testimonial declaration in telematic hearings: Challenges and advantages in the Ecuadorian judicial system - Arguello Bajaña, Daniel Alfredo (2025)
The testimonial declaration in telematic hearings has revolutionized the Ecuadorian judicial system, offering both advantages and significant challenges. The objective of the study is to analyze the testimonial declaration procedure in telematic hearings in the civil sphere, with emphasis on the judicial system in Guayaquil, Ecuador. It is a legal investigation with a mixed focus, with an analysis of legal regulations and jurisprudence related to the testimonial declaration in telematic hearings within civil courts. The techniques and instruments provided direct observation and guide to surveys with closed questions applied to new lawyers specializing in the civil area. The results show a lack of clarity, which is partly due to the absence of specific legislation on how testimonial statements should be carried out in telematic hearings. It is concluded that, the investment in technology, the continued training of judicial operators and clear and updated regulation are the pillars for the success of the telematic modality